Some aspects of the ecology of the citrus red mite, Panonychus citri (McGregor), in the Eastern Cape Province - Keetch, D P (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1969)
The citrus red mite, Panonychus citri (McGregor), is a relatively new pest to South African citriculture, the first recorded injury to citrus trees was from Rustenberg, Transvaal in 1950 (Smith 1953). In the U.S.A. the biology of this mite has been studied by Quayle (1938), Prendergast (1938), English and Turnipseed (1941), DeBach (1947), DeBach et al. (1950), Ebeling (1959) and Jeppson et al. (1957,1961). However, in South Africa little information is available concerning the ecolopy of the citrus red mite. The majority of the literature pertaining to P. citri in Republic, (Smith (1953), Mentz (1954), Stofberg (1959), Schwartz (1965) and Brodrick (1965) is of a descriptive nature, and mainly concerned with the chemical control of the mite. The only biological investigation on the development of P.citri, and the effect of insecticides and insect predators on its biology, under South African conditions, was made by van Rooyen (1966) at Zebediela, Transvaal. In the control of citrus pests, such as the citrus red mite, that need for a better understanding of their ecology has been well emphasised by DeBach (1951) and Griffiths (1951). DeBach (1951) in particular, stressed the danger of the continued reliance on insecticidal treatment as the only method of nest control, and has pointed out that persistent chemical applications may only serve to intensify the pest problem. He has suggested that a closer study of the environment of the pest species could provide a solution to the problems now encountered as a result of insecticidal control measures. Intro., p. 1-2.
Keywords: Citrus -- Diseases and pests -- South Africa -- Eastern Cape; Plant mites -- Ecology -- South Africa; Citrus red mite; Citrus red mite -- Ecology